High performance cross-linked anion exchange membrane based on aryl-ether free polymer backbones for anion exchange membrane fuel cell application. Issue 8 (10th June 2020) - Gao, Xueqiang; Yu, HongMei; Xie, Feng; Hao, Jinkai; Shao, Zhigang
Abstract : Anion exchange membrane fuel cells (AEMFCs) have attracted growing interest in recent years due to the favored electrochemical kinetics of the oxygen reduction reaction (ORR) and potential low cost, and development of high performance AEMs is always an urgent issue. Abstract : Anion exchange membrane fuel cells (AEMFCs) have attracted growing interest in recent years due to the favored electrochemical kinetics of the oxygen reduction reaction (ORR) and potential low cost, and development of high performance AEMs is always an urgent issue. In this work, a series of cross-linked AEMs with different diamine cross-linkers and various degrees of crosslinking based on the aryl-ether free tri-block copolymer SEBS were prepared using an in situ crosslinking method. FT-IR, XRF and EDS spectra confirm the structures and the degree of crosslinking of the AEMs. Moreover, the cross-linked AEMs demonstrated good mechanical properties and dimensional stability; the tensile strength reached 18.43 MPa ( ca. 4.5 times higher than that of the membrane without crosslinking), and the swelling ratios of the cross-linked AEMs were only ca. 10%, which meet the requirement of the AEMFC application. In addition, the cross-linked AEMs demonstrated high ionic conductivity at relatively low IECs and water uptake, and the results of SAXS and TEM verified that the high conductivity could be attributed to the good hydrophilic/hydrophobic phase separation microstructure. Furthermore, in the test of H2 /O2 AEMFCs, the MEAs fabricated using the cross-linked membranes displayed good fuel cell performance, especially for the C4 -CQASEBS membrane, and the fuel cell realized a peak power density of 585 mW cm −2 at 60 °C. The results indicated that the cross-linked AEMs based on SEBS are a promising candidate material for fuel cell application.